Policy Implementation Handling Stunting In Bogor District West Java Province - Masturina, Masruroh Luthfiah; Ilham, Muh.; Kurniawati, Layla (Al Makki Publisher, 2025)
The stunting prevalence rate in Indonesia is still relatively high when compared to neighboring countries such as Malaysia and Singapore in 2021. Then Presidential Regulation Number 72 of 2021 was born as an effort to accelerate the reduction in stunting prevalence. Bogor Regency is one of the Autonomous Regions in West Java Province which also contributes to the high stunting prevalence rate, through Regent Instruction number 440/884 of 2019 concerning Integrated Stunting Intervention with the aim of reducing stunting rates. The purpose of this study is to analyze the Implementation of Stunting Handling Policies in Bogor Regency, West Java Province. To analyze the Implementation of Stunting Handling Policies in Bogor Regency, West Java Province, researchers used Hamdi's theory of public policy implementation which consists of Productivity, Linearity, and Efficiency. The method used in this research is descriptive research with a qualitative approach, namely by describing and analyzing the Implementation of Stunting Handling Policies in Bogor Regency, West Java Province. The data collection techniques used are interviews, observation, and documentation. The results showed that the implementation of stunting handling policies in Bogor Regency, West Java Province, has been running well from the aspects of productivity, linearity, and productivity. This can be seen from the decline in stunting prevalence from 27.6% to 7.59%. However, there are several determinant factors that influence the unsuccessfulness of Policy Implementation such as budget constraints, therefore the author suggests the Bogor Regent to make a Regent's regulation regarding the priority use of the budget each year.